PENGARUH PEMBERIAN EKSTRAK ETANOL RIMPANG LENGKUAS (ALPINIA GALANGA) TERHADAP GAMBARAN HISTOPATOLOGI HEPAR MENCIT (MUS MUSCULUS L.) YANG DIINDUKSI MONOSODIUM GLUTAMATE - Theodora Agverianti; Muhartono Muhartono; Khairun Nisa Berawi (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2019)
ABSTRACT Background: Long term consumption of Monosodium Glutamate (MSG) in excess isreported induced liver damage. Toxic effect in liver are due to the degeneration andnecrosis of hepatocytes, which also increases lipid peroxidation. Antioxidant in galangal rhizome is expected to repair liver damage caused by free radicals in MSG. Method: This study is an experimental research with Post Test Only Control Group Design. The samples in this study are 25 mice divided into 5 groups which are, negative control (not given any treatment), positive control (given MSG 4 mg/gBW for 14 days), treatment 1 (given MSG 4 mg/gBW for 14 days continued with ethanol extract of galangal rhizome 14 mg/20 gBW for7 days), treatment 2 (given MSG 4 mg/gBW for 14 days continued with ethanol extract of galangal rhizome 28 mg/20 gBW for 7 days), and treatment 3 (given MSG 4 mg/gBW for 14 days continued with ethanol extract of galangal rhizome 56 mg/20 gBW for 7 days). Then surgery was needed for histopathological examination. Results: Based on mean scoring results, the results showed calculation of liver cell degeneration for positive control (11,8), negative control (5,2), treatment 1 (10,6), treatment 2 (8,4), and treatment 3 (7,6). Based on the test results One Way ANOVA, the result showed the value of p=0,001 for liver histopathological appearance of mice. Conclusion: There is an effect of ethanol extract of galangal rhizome to the liver histopathological appearance of male mice.